Strength Characteristics and Material Design of Recycled Flexible Pavement Materials - Bubpi, Attaphol; Arngbunta, Anukun; Amornpinyo, Prach; Sirisriphet, Yongyuth; Tho-In, Tawatchai; Srichandum, Sakchai; Srirueng, Preechawut; Kampala, Apichit; Posi, Patcharapol; Chindaprasirt, Prinya (Civil Engineering Journal, 2025)
This study develops a strength-based mix-design framework for rehabilitating flexible pavements using reclaimed asphalt pavement (RAP) blended with crushed rock (CR) and cement. Objectives were to quantify 7-day unconfined compressive strength (UCS) as a function of mixture variables and to provide field-ready proportioning equations. Methods comprised laboratory testing of RAP–CR blends (RAP = 0–100%) with 2–5% cement, Modified Proctor compaction, and 7-day UCS; regression related UCS to a modified parameter (w/c)(1−k·AS), where asphalt content (AS) is obtained from AS = 0.04·RAP. Findings show that increasing RAP lowers dry density (2.31→2.11 g/cm³) and raises optimum moisture (5.03→7.17%). The 7-day prediction is qᵤ,7 = 23.44/[(w/c)(1−0.22·AS)]0.677 (R² = 0.863). A worked example (4-cm asphalt over a 20-cm base; 20-cm milling) gives RAP = 20%, AS = 0.80, recommended w/c = 1.31, and cement = 4.03% at OMC = 5.28% and dry density = 2.276 g/cm³, satisfying 1.72 MPa (17.5 kg/cm²) at 7 days. Novelty/Improvement: the framework consolidates RAP content and binder effects into a single modified w/c parameter, enabling rapid, transparent proportioning for construction control. Broader impacts include reduced demand for virgin aggregate and haul-off of demolition debris, fewer truck movements and landfill burdens, and potential life-cycle cost savings in network-level rehabilitation.